2019
DOI: 10.1002/ajs4.96
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Land, family and culture for a good life: Remote Aboriginal people with disability and carers

Abstract: Worldwide health and social outcomes of Indigenous people are poorer than those of non‐Indigenous. In Australia, the Indigenous population experience disability at more than twice the rate of the non‐Indigenous population, and a quarter live in geographically remote areas. The challenges associated with accessing services and supports in remote communities can impact on a good life for Aboriginal people with disability. Interviews were conducted with Aboriginal people (Anangu) with disability and family carers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…A non-Aboriginal Community Controlled Health Service led approach to NDIS implementation with Aboriginal and Torres Strait Islander communities in the Northern Territory and Queensland found that attempts from the NDIA to engage with communities had been perceived as cursory, inappropriate, and ineffective by the communities they sought to engage with [41]. In contrast, an Aboriginal Community Controlled Health Service led approach in remote Central Australia found that a model where Aboriginal coworkers worked alongside disability workers was effective in delivering culturally safe and acceptable services to Aboriginal people with a disability [18,19]. Our study contributes to an evidence base that demonstrates the importance of Aboriginal Community Controlled responses in achieving equitable access for remote Aboriginal people with a disability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A non-Aboriginal Community Controlled Health Service led approach to NDIS implementation with Aboriginal and Torres Strait Islander communities in the Northern Territory and Queensland found that attempts from the NDIA to engage with communities had been perceived as cursory, inappropriate, and ineffective by the communities they sought to engage with [41]. In contrast, an Aboriginal Community Controlled Health Service led approach in remote Central Australia found that a model where Aboriginal coworkers worked alongside disability workers was effective in delivering culturally safe and acceptable services to Aboriginal people with a disability [18,19]. Our study contributes to an evidence base that demonstrates the importance of Aboriginal Community Controlled responses in achieving equitable access for remote Aboriginal people with a disability.…”
Section: Discussionmentioning
confidence: 99%
“…The NDIA Rural and Remote Strategy [16] and Aboriginal and Torres Strait Islander Engagement Strategy [17] outline how the NDIA aims to engage with Aboriginal and Torres Strait Islander people in culturally appropriate ways [16,17]. These documents provide valuable foundations and demonstrate that the NDIA is cognisant that Aboriginal and Torres Strait Islander access in remote and regional Australia demands innovation, investment, and partnerships [18][19][20]. They do not, however, provide information to guide the implementation of the NDIS at a practical level.…”
Section: Introductionmentioning
confidence: 99%
“…Kana’iaupuni (2005) describes an Indigenous Hawaiian ‘world‐view’, which privileges connection to genealogy and land, and values reciprocity and inclusion, and in which Elders guide families and community and are seen as the keepers of traditional knowledges. Such a world‐view shares features with those of other Indigenous peoples where subjectivity is characterised by an equal and mutual relationship with the land (Dew et al, 2019; Fredericks, 2013; Hatala et al, 2019; Kulis et al, 2013; Moreton‐Robinson, 2013), underpinned by kinship structures that affirm place in family and community (Rountree & Smith, 2016; Van Uchelen et al, 1997; Yap & Yu, 2016), and in which collective good is valued over individual wellbeing. In this literature, ‘cultural identity’ is seen to be relational—to land, ancestry, kinship and community—in a way that is not captured by the ‘culture as treatment’ models described earlier.…”
Section: Sociocultural Approaches: Building On Collective Strengthsmentioning
confidence: 99%
“…Islander culture and so the potential impact of infertility might well be expected to have a significant emotional impact in these groups. 9 The importance of culturally safe health care is widely recognized, and the provision of appropriate care is likely to be even more important when very personal issues such as infertility and incontinence are discussed with Aboriginal and Torres Strait Islander women. 10 Indeed, studies of non-Indigenous women 11 note the close relationship between shame and urinary incontinence:…”
Section: Families Are a Very Important Part Of Aboriginal And Torres ...mentioning
confidence: 99%
“…Families are a very important part of Aboriginal and Torres Strait Islander culture and so the potential impact of infertility might well be expected to have a significant emotional impact in these groups 9 …”
Section: Introductionmentioning
confidence: 99%